Research progress on the mechanism of ferroptosis and its role in diabetic retinopathy - He, Wei; Chang, Lu; Li, Xinlu; Mei, Yan (Frontiers in Endocrinology, 2023)
Ferroptosis is iron-dependent regulatory cell death (RCD). Morphologically, ferroptosis is manifested as mitochondrial atrophy and increased mitochondrial membrane density. Biochemically, ferroptosis is characterized by the depletion of glutathione (GSH), the inactivation of glutathione peroxidase 4 (GPX4), and an increase in lipid peroxides (LPO)and divalent iron ions. Ferroptosis is associated with various diseases, but the relationship with diabetic retinopathy(DR) is less studied. DR is one of the complications of diabetes mellitus and has a severe impact on visual function. The pathology of DR is complex, and the current treatment is unsatisfactory. Therefore, exploring pathogenesis is helpful for the clinical treatment of DR. This paper reviews the pathological mechanism of ferroptosis and DR in recent years and the involvement of ferroptosis in the pathology of DR. In addition, we propose problems that need to be addressed in this research field. It is expected to provide new ideas for treating DR by analyzing the role of ferroptosis in DR.